2003
DOI: 10.1089/107662903764736283
|View full text |Cite
|
Sign up to set email alerts
|

Study of Developed Resistance Due to Antibiotic Treatment of Coagulase-Negative Staphylococci

Abstract: Coagulase-negative Staphylococci (CoNS) are a major cause of postoperative infections. These infections are often associated with foreign material implants and/or a compromised immune system in the patient. Multiresistant strains are increasingly common in the hospital environment and there is concern that the infections will become difficult or impossible to treat. This report is based on a study of 75 patients, with postoperative infections caused by CoNS after thoracic surgery. All patients were treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Noguchi et al [ 22 ] detected qacA/B genes in 14.0% and smr genes in 28.0% of 71 clinical MRSA isolates in Japan. Alam et al [ 29 ] reported that in 522 clinical S. aureus isolates from a hospital in Japan, qacA/B was more prevalent in MRSA (32.6%) and more prevalent in MSSA (7.5%) than smr genes, which had a frequency of 3.3% in MRSA and 5.9% in MSSA.…”
Section: Discussionmentioning
confidence: 99%
“…Noguchi et al [ 22 ] detected qacA/B genes in 14.0% and smr genes in 28.0% of 71 clinical MRSA isolates in Japan. Alam et al [ 29 ] reported that in 522 clinical S. aureus isolates from a hospital in Japan, qacA/B was more prevalent in MRSA (32.6%) and more prevalent in MSSA (7.5%) than smr genes, which had a frequency of 3.3% in MRSA and 5.9% in MSSA.…”
Section: Discussionmentioning
confidence: 99%
“…The high mortality rate related to staphylococcal infections [12], the increase in S. aureus isolates resistant to antibiotics [13], and frequent and prolonged exposure to antimicrobial agents hinder the treatment of infections [14]. Therefore, alternative strategies to prevent or treat infections caused by S. aureus , sometimes minimizing or supplementing use of antibiotics, are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports [3][4][5] show continuing increases in staphylococcal resistance to currently available antimicrobial agents. Frequent and prolonged exposure to antimicrobials have been demonstrated to increase the risk of developing infections with resistant organisms [5,6]. Therapeutic products and strategies that could prevent infections would minimize the need for antimicrobial products and thereby potentially diminish the emergence of resistant organisms.…”
Section: Introductionmentioning
confidence: 99%